Jogo de espelhos: realidade fantástica e revolução em Cortázar - Rocha, Alana Rúbia Stein (2012)
This study aims to approach three Cortázars narratives ( Recortes de Prensa , Apocalipsis de Solentiname e Continuidad de los parques ) from the perspective of other literary and extra literary productions (letters, critics and theory texts) by Julio Cortázar. This is an experimentation of a ludic study, according to the proposal of the Argentine authors literature, embedded in the idea of the game as a different way of seeing reality and, through this way, make effective changes in the modern world, being they political, or personal. By using this method, we plan to verify the critical and self-critical content of Cortázars literature, to emphasize its political and pragmatic aspects when it comes to the revolution of human perspective and behavior through written art. To do so, we confronted texts chosen as corpus with other writings, also written by Cortázar, trying to make the latter to act as an enlightening component to his literature. In other words, this study evaluates the texts by the author in his ambiguous quality, which embraces both literature and critical (and, in many cases, theoretical)literature. The tales approached by this study are analyzed under three different perspectives, which are: the question of political responsibility of the Latin American writer, the self-writing and the fiction in their relations with the factual and its writing and literature itself in its relations with the factual and imaginary, and, finally, the position of the reader and author before the literary text. Both discussions raised during the analysis have a common thematic point, which converges to problematization of the common construction of an immediate reality rooted in philosophical and scientific manner of the modern Western world. Finally, the study experiments a different look at the literary text, regarding its construction, its interpretation and its effects on reality.